Identification and Characterization of Secondary Wall-Associated NAC Genes and Their Involvement in Hormonal Responses in Tobacco (Nicotiana tabacum) - Xu, Na; Meng, Lin; Song, Lin; Li, Xiaoxu; Du, Shasha; Hu, Fengqin; Lv, Yuanda; Song, Wenjing (Frontiers in Plant Science, 2021)
The secondary wall-associated NAC genes (SWNs) are a subgroup of NAC (NAM, ATAF, and CUC) transcription factor which play a key role in regulating secondary cell wall biosynthesis in plant. However, the gene family has not been systematically characterized and their potential roles in response to hormones is unknown in Nicotiana tabacum. In our study, a total of 40 SWN genes including 12 from N. tomentosiformis, 13 from N. Sylvestris, and 15 from N. tabacum were successfully identified and classified into three groups including vascular-related NAC domain genes (NtVNDs), NAC secondary wall thickening promoting factor genes (NtNSTs) and secondary wall-associated NAC domain genes (NtSNDs). The protein characteristic, gene structure and chromosomal location of 15 NtSWNs (also named as Nt1 to Nt15) were also analyzed. NtVND and NtNST group genes had five conserved subdomains in their N-terminal regions and a motif (LP[Q/x]L[E/x]S[P/A]) in their diverged C- terminal regions. Some hormones, dark, and low-temperature related cis-acting elements were significantly enriched in the promoters of NtSWN genes. Comprehensive expression profile analysis revealed that Nt4 and Nt12 might play a role in vein development, others might be important for stem development. qRT-PCR revealed NtNST group genes such as Nt7, Nt8, and Nt13 showed more sensitive than NtVND group genes and NtSND group genes under hormones and abiotic stresses. Transactivation assay further suggested Nt7, Nt8 and Nt13 showed significant transactivation activity. Overall, SWN genes were finally identified and characterized in diploid and tetraploid tobacco, revealing new insights into their evolution, variation and homology relationships. Transcriptome, cis-acting element, qRT-PCR and transactivation assay analysis indicated the roles in hormonal and stress responses, which provided further resources into molecular mechanism and genetic improvement.